1977
DOI: 10.1017/s002531540002124x
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of heavy-metal contamination in the Looe Estuary (Cornwall) with particular regard to silver and lead

Abstract: A map of the Looe Estuary in south-east Cornwall is shown in Fig. 1. As it flows to the western branch of the estuary, the West Looe River passes through the Herodsfoot mining area which lies about 5 km above Sowden's Bridge. By Cornish standards, this was a productive area for lead and Dewey (1921) gives the output of Herodsfoot mine as 13470 tons of metal between 1848 and 1884 and more than 17 tons of silver between 1853 and 1884.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(26 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Bryan & Hummerstone (1977) found that the pattern of silver accumulation in several organisms from the Looe Estuary, UK, varied between species. Macroalgae and the herbivorous limpet Patella vulgata exhibited little variation in silver concentrations with distance upriver, while filter-feeders such as the cockle Cerastoderma edule exhibited elevated silver levels in upriver locations.…”
Section: Discussionmentioning
confidence: 97%
“…Bryan & Hummerstone (1977) found that the pattern of silver accumulation in several organisms from the Looe Estuary, UK, varied between species. Macroalgae and the herbivorous limpet Patella vulgata exhibited little variation in silver concentrations with distance upriver, while filter-feeders such as the cockle Cerastoderma edule exhibited elevated silver levels in upriver locations.…”
Section: Discussionmentioning
confidence: 97%
“…Analysis of the copper content of mussel digestive glands was based on the methods of Bryan & Hummerstone (1971, 1977 and involved acid digestion of groups of 7 portions of digestive gland per age group and sampling time. This was followed by atomic absorption using a Pye Unicam SP9 spectrophotometer at a wavelength of 324.8 nm with an airacetylene flame, background correction and external standards.…”
Section: Methodsmentioning
confidence: 99%
“…Species commonly used include tittorina sp., Patella sp., Mytilus edulis, Scrobicularia plana, Macoma sp., Nucella sp., and Nereis sp. All these organisms may concentrate heavy metals up to several thousand times the concentration in the water column (see Bryan & Hummerstone, 1977). Therefore, provided sufficient material can be collected, heavy-metal concentrations can be easily and accurately established.…”
Section: The Faunamentioning
confidence: 99%
“…Pollution Load Indices have also been derived using published data for the Bristol Channel (Fuge & James, 1974), the Looe Estuary, Cornwall (Bryan & Hummerstone, 1977) and a polluted (Serfjorden) and unpolluted (Reine in Lofoten) estuary in Norway (Melhuus et al, 1978). Values of 3.8,7.4,29.0 and 3.1,respectively, suggest that with the exception of the copper polluted Avoca estuary at Arklow (Fig.…”
Section: Indices For Pollution Assessmentmentioning
confidence: 99%